Eclecticism in child welfare - Terje Halvorsen (Journal of Comparative Social Work)
This article discusses the use of professional theories in the field of child welfare. The presentation is largely based on the author’s observations from debates between Norwegian scholars over the last four decades. The conclusion, however, may have a general validity. During previous century a large number of theories were introduced to the field of child welfare. When we reached the end of the century there was a multitude of available theories, but also strong disagreement among peers about which theory to choose. Several researchers then advocated a clean-up campaign where one through randomized controlled trials should decide which theories are true and which methods work. False theories and ineffective methods were to be discarded. The researchers, however, experienced problems and disappointments. It proved hard to demonstrate that a particular method had decisive impact on most children and young people. The author argues that one should give up the search for one ultimate approach, or a few preferred approaches, and realize that eclecticism is the way to high-quality child welfare.